2002
DOI: 10.1038/sj.onc.1205883
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of AP-1 transcription factor causes blockade of multiple signal transduction pathways and inhibits breast cancer growth

Abstract: AP-1 transcription factors play a critical role in signal transduction pathways in many cells. We have investigated the role of AP-1 in controlling proliferative signals in breast cells, and have previously shown that AP-1 complexes are activated by peptide and steroid growth factors in both normal and malignant breast cells. In this study, we investigated the role of AP-1 in transducing proliferative signals induced by peptide and steroid growth factors. We used MCF-7 clones that express a specific inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
3
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 32 publications
3
103
3
2
Order By: Relevance
“…AP-1 blockade causes decreased expression of D and E cyclins, the main cyclins in G1 phase of cell cycle, and These changes in the expression of cell cycle regulators leads to reduced CDK2 and CDK4 activity, which in turn causes hypophosphorylation of Rb and inhibition of E2F activity, ultimately inducing a G1 cell cycle block. In combination with our previous results showing that expression of TAM67 blocks signal transduction by multiple growth factors (Liu et al, 2002), these studies demonstrate that AP-1 blockade can effectively block signal transduction and inhibit the growth of breast cancer cells. We and others have previously shown that AP-1 transcription factors are critical for cell proliferation and transformation of several cell types (Holt et al, 1986;Brown et al, 1994;Chen et al, 1996a;Liu et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…AP-1 blockade causes decreased expression of D and E cyclins, the main cyclins in G1 phase of cell cycle, and These changes in the expression of cell cycle regulators leads to reduced CDK2 and CDK4 activity, which in turn causes hypophosphorylation of Rb and inhibition of E2F activity, ultimately inducing a G1 cell cycle block. In combination with our previous results showing that expression of TAM67 blocks signal transduction by multiple growth factors (Liu et al, 2002), these studies demonstrate that AP-1 blockade can effectively block signal transduction and inhibit the growth of breast cancer cells. We and others have previously shown that AP-1 transcription factors are critical for cell proliferation and transformation of several cell types (Holt et al, 1986;Brown et al, 1994;Chen et al, 1996a;Liu et al, 2002).…”
Section: Discussionsupporting
confidence: 52%
“…We have also demonstrated that TAM67 inhibited breast cancer growth both in vivo and in vitro (Liu et al, 2002). These studies suggest that AP-1 transcription factor is an important regulator of breast cancer cell growth, invasion, and resistance to antiestrogens.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…With respect to the mechanism of TAM resistance, it has been reported that breast carcinoma cells can undergo hormoneindependent growth and, in turn, growth factor-dependent growth activated by the transcription factor AP-1. 38 Overexpression of HER-2 is observed in TAMresistant cells, 39 and treatment with trastuzumab overcomes this resistance. 40 Moreover, TAM resistance also is induced by overexpression of Akt and Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…1 The expression of c-jun is also constitutively increased in many other transformed cell lines 6,7 and human cancers. [8][9][10] Further, a direct jun amplification and overexpression has recently been demonstrated in aggressive human sarcomas. 11 Additionally, c-Jun is a central mediator of the activity of many oncogenes activated in human tumors.…”
mentioning
confidence: 99%